The Practice of Research on Migration and Mobilities - Rivera-Sánchez, Liliana; Lozano-Ascencio, Fernando (Migration Studies, 2014)
The migration process is interpreted in a different way when researchers live in so-called societies of origin, than when it is interpreted from societies of destination-even when research work is multi-situated. The localization of researchers in this field involves numerous factors that influence the modalities for conducting research. Research agendas are clearly mediated by these localizations, and this book on the contemporary social sciences points out those mediations, breaking with the dichotomous readings that are implicit in this migration process (origin-destination, north-south, and cause-effect, to mention just a few). In the individual chapters, priority is given to presenting the modalities through which research is conducted in multidisciplinary or interdisciplinary teams on the American Continent. In summary, the focus of this book is on the narrative of methodological experience of the Practice of Research on Migration and Mobilities.